2015
DOI: 10.1016/j.epsl.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Seismic evidence for a chemically distinct thermochemical reservoir in Earth's deep mantle beneath Hawaii

Abstract: Nearly antipodal continent-sized zones of reduced seismic shear wave velocities exist at the base of Earth's mantle, one beneath the Pacific Ocean, the other beneath the South Atlantic Ocean and Africa. Geophysicists have attributed the low velocity zones to elevated temperatures associated with large-scale mantle convection processes, specifically, hot mantle upwelling in response to cooler subduction-related downwelling currents. Hypotheses have included superplumes, isochemical heterogeneity, and stable as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…Our results are consistent with the inference of steeper sides of the West Pacific anomaly. Zhao et al (2015) analyse the same anomaly beneath the northern Pacific using observations of waveform broadening and suggest it extends to 600-900 km above the CMB and also argue that it has shallowly sloped sides. The specific geometries used by He & Wen (2012) and Zhao et al (2015) constrain the shallow slopes only on the northern and eastern edge of this anomaly.…”
Section: Comparison With Regional Seismic Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are consistent with the inference of steeper sides of the West Pacific anomaly. Zhao et al (2015) analyse the same anomaly beneath the northern Pacific using observations of waveform broadening and suggest it extends to 600-900 km above the CMB and also argue that it has shallowly sloped sides. The specific geometries used by He & Wen (2012) and Zhao et al (2015) constrain the shallow slopes only on the northern and eastern edge of this anomaly.…”
Section: Comparison With Regional Seismic Studiesmentioning
confidence: 99%
“…Zhao et al (2015) analyse the same anomaly beneath the northern Pacific using observations of waveform broadening and suggest it extends to 600-900 km above the CMB and also argue that it has shallowly sloped sides. The specific geometries used by He & Wen (2012) and Zhao et al (2015) constrain the shallow slopes only on the northern and eastern edge of this anomaly. Our vote map suggests that this anomaly, which we dubbed the Superswell anomaly, does indeed have shallowly sloped sides, but also continues further to the south where it extends throughout the lower mantle (Fig.…”
Section: Comparison With Regional Seismic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of high-resolution, forward modelling seismic studies have shown that shear waves travelling in the deep mantle near LLSVP edges become broadened and/or shifted in time 2,5,[9][10][11] . This is consistent with a phenomenon called multi-pathing, where a seismic wave incident on strong heterogeneity can parse into energy that travels through the heterogeneity, as well as energy that refracts around it.…”
mentioning
confidence: 99%
“…Long-lived thermochemical mantle upwellings (e.g. Zhao et al, 2015) could continuously advect peridotite that is oxidising enough to enable redox melting at 250 km depth. Alternatively, low-density methane-rich fluids continually rising from the deep upper mantle and transition zone could be oxidised at the depth of metal saturation, providing a continuous supply of reduced carbon from which carbonated melt could be generated near the base of thick lithospheres (Rohrbach et al, 2007;Frost and McCammon, 2008;Rohrbach and Schmidt, 2011) (Fig.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%